Zinner syndrome in a case of male infertility: a case report - M., Rashika; Jain, Vishal; Netam, S. B. S.; Verma , Ghanshyam (International Surgery Journal, 2024)
Zinner syndrome is a rare congenital malformation formed by the developmental anomaly of distal portion of the wolffian duct. It is an unusual cause of infertility and dysuria among young males. It is associated with ipsilateral renal agenesis, seminal vesical cyst, and ejaculatory duct obstruction. We herein report a rare case of a Zinner syndrome, in a patient of primary infertility. He also presented with complaints of chronic pelvic pain and dysuria. Any young patients of male infertility or unspecified pelvic complaints should be evaluated for Zinner syndrome and surgical intervention is the mainstay treatment for symptomatic patients.